PERANCANGAN SISTEM INFORMASI PENYIMPANAN REKAM MEDIS RAWAT INAP BERBASIS ELEKTRONIK - Sali Setiatin; Yuda Syahidin (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
This research aims to produce a system of record-keeping information of Medical Record in Hospital. System device used the development of waterfall.This research found several problems in the processing of medical records storage in Hospital, namely : (1). Storage processing of inpatient medical records have been computerized, but the recording was still using Microsoft Excel so that takes time was relatively long ; (2). Sometimes the data were fed inaccurate ;(3). The duplication of data.The suggestion was given : (1). Training and understanding of the clerk in the process and operate the report ;(2). Information system is easy to creating operate so that the officers have that has been processed from microsoft excel but to make a report with the data that has been processed.